Race Relations in Halifax, Nova Scotia, During the Mid-Victorian Quest for Reform - Sutherland, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1996)
AbstractThis paper explores the dynamics of race in Nova Scotia's capital city through the 1840s and early 1850s. Black Haligonians actively sought to escape a legacy of marginalisation through participation in the politics of reform, which involved a dual struggle against oligarchy in Nova Scotia and slavery in America. White society responded with a contradictory blend of accommodation and resistance. Eventually, segregation, rather than integration, prevailed, a result that reflected white prejudice more than black preference.